Past, Present, and Future of European Union’s Judicial Architecture - Norkus, Rimvydas (Teisė, 2024)
This article delves into the essential conditions for the transfer of jurisdiction from the Court of Justice to the General Court to hear and determine questions referred for a preliminary ruling in specific areas. Against the backdrop of the ongoing legislative process aimed at implementing Article 256(3) of the Treaty on the Functioning of the European Union, the article examines proposed legislative changes to the Statute of the Court of Justice of the European Union. Furthermore, the article explores potential practical implications associated with these legislative amendments, shedding light on their anticipated applications.